2018
DOI: 10.1186/s12933-018-0744-6
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of cherry consumption as a dietary intervention for metabolic, hepatic and vascular complications in type 2 diabetic rats

Abstract: BackgroundOxidative stress (OS) plays an important role in type 2 diabetes (T2D) pathogenesis and its complications. New therapies target natural antioxidants as an alternative and/or supplemental strategy to prevent and control them. Our previous chemical and biological studies highlighted the important antioxidant activities of cherries, among other fruits and vegetables, thus we aimed to determine in vivo effects of 2-month long cherry consumption using a high-fat/high-fructose (HFHF) model of diabetic-rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 106 publications
1
16
0
Order By: Relevance
“…It is generally assumed that the criteria used for rats are closest to those used for humans, namely, FBG > 126 mg/dl (7.0 mmol/L). 158,159 In contrast, the basal levels of FBG in mice are higher than those in rats and humans (ranging between 140 and 220 mg/dl), indicating that according to the aforementioned criteria, all mice would develop diabetes. Hence, FBG values ≥250 mg/dl is the recommended threshold for defining T2DM in mice.…”
Section: Prediabetesmentioning
confidence: 99%
“…It is generally assumed that the criteria used for rats are closest to those used for humans, namely, FBG > 126 mg/dl (7.0 mmol/L). 158,159 In contrast, the basal levels of FBG in mice are higher than those in rats and humans (ranging between 140 and 220 mg/dl), indicating that according to the aforementioned criteria, all mice would develop diabetes. Hence, FBG values ≥250 mg/dl is the recommended threshold for defining T2DM in mice.…”
Section: Prediabetesmentioning
confidence: 99%
“…Although several pathways of diabetic hepatic lesions have been identified, oxidative stress, and ROS production are still the main cause. Antioxidant therapy might be an effective treatment for ameliorating diabetic hepatic damage (Polce et al., 2018; Simões et al., 2013; Van der Werf et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of fruit and leaves to the HFr diet also caused improvement of the lipid profile in the serum (Table 2). Der Werf et al [13] observed the beneficial effect of consumption of sweet cherry fruit in rats fed with high-fat/high-fructose diet, i.e., decrease in the hepatic lipid accumulation, as well as reduction in cholesterol and triglycerides level in the serum. We suppose that the bioactive compounds contained in fruit and leaves of sweet cherry (dietary fiber, carotenoids, polyphenols) [15,16] can be responsible for this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Gibert-Ramos et al [37], who assessed the effect of sweet cherry fruit on lipid metabolism and fat accumulation in Fischer rats treated with 1:1 glucose:fructose solution in water, have also observed that intake of fruit downregulated the expression of Fasn and Acaca in the adipose tissue. Der Werf et al [13] have shown that the addition of fruit to high-fat/high-fructose diet caused the reduction in hepatic lipogenic transcription factors: ChREBP ( Mlxipl) and Srebp . We suppose, that anthocyanins contained in fruit may be responsible for this activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation